2010
DOI: 10.1148/rg.304095150
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT versus CT, MR Imaging, and67Ga Scintigraphy in the Posttherapy Evaluation of Malignant Lymphoma

Abstract: Malignant lymphoma is the most common form of hematologic cancer, yet because of advanced methods of assessment, the traditional histology-based classification of lymphoma is insufficient for understanding lymphoma imaging. Still, radiologists should be familiar with the imaging findings in lymphoma. Integrated positron emission tomography (PET)-computed tomography (CT) allows improved diagnostic accuracy, and uptake of 2-[fluorine-18]fluoro-2-deoxy-D-glucose (FDG) can help predict response during treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 62 publications
0
34
0
1
Order By: Relevance
“…kilovoltage peak) i rozdzielczości przestrzennej 5mm. Akwizycję PET całego ciała oraz regionu głowy i szyi przeprowadzono badając kolejne odcinki ciała z czasem akwizycji 1min 30 s na odcinek, przy zastosowaniu korekty pochłaniania i korekty rozpadu promieniotwórczego [28][29][30][31][32].…”
Section: Materiał I Metodaunclassified
“…kilovoltage peak) i rozdzielczości przestrzennej 5mm. Akwizycję PET całego ciała oraz regionu głowy i szyi przeprowadzono badając kolejne odcinki ciała z czasem akwizycji 1min 30 s na odcinek, przy zastosowaniu korekty pochłaniania i korekty rozpadu promieniotwórczego [28][29][30][31][32].…”
Section: Materiał I Metodaunclassified
“…Several studies have shown that standardized uptake value correlates with the degree of malignancy in lymphomas, and in patients with NHL and an standardized uptake value greater than 10 are quite likely to have aggressive disease (Okada M et al, 2010). The degree of FDG uptake by lymphoma cells may be a biomarker for disease biology: e.g.…”
Section: Fdg-petmentioning
confidence: 99%
“…HL and the more aggressive forms of NHL share similar radiologic imaging patterns with the near universal use of combined FDG-PET/CT for assessment [6, 7]. Combined FDG-PET/CT is now considered the most accurate tool for diagnosis, assessment of treatment response, and prognosis in patients with aggressive NHL [8]. There are a number of caveats that one must be aware of when interpreting FDG-PET/CT in the setting of lymphoma.…”
Section: Imaging Considerations In Lymphomamentioning
confidence: 99%